Determination of airborne bacteria and fungi in the laboratories of a university - Muangsue, Noppadon; Amimanan, Piyawan (Health Science, Science and Technology Reviews, 2018)
Air quality of indoor environmental is an important factor affect to health of people. The aim of the study was to determine amount and types of airborne bacteria and fungi in the laboratories of a university. The open plate technique was used to collect samples in the morning and afternoon for 3 weeks. The result showed that the average amounts of bacteria and fungi were 67.6 to 340.5 and 69.6 to 370.8 CFU/dm2/h, respectively. The evaluations of the index of microbial air contamination (IMA) were fair to very poor. However, the concentrations of airborne bacteria and fungi were not higher than proposed air quality index. Therefore, air quality of university laboratories had good hygienic standard. Type of bacteria and fungi were found to include Micrococcus spp., gram negative bacilli, Bacillus spp., Penicillium spp., Curvularia spp., Rhizopus spp. and Cladosporium spp., respectively.